STRATEGI PENGAWASAN APARATUR SIPIL NEGARA DI KABUPATEN ACEH BARAT - Nike Juseprita (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2023)
This research is about the ASN supervisory strategy by the West Aceh District BKPSDM. strategy is an idea that is arranged before carrying out an action or action in doing something so that what is the goal can be achieved. So that the results achieved are maximized and efficient before taking an action there must be a strategy used. This study aims to see how far the strategy has been carried out by BKPSDM towards ASN. This research uses qualitative research methods and data collection is carried out through interviews, observation, and documentation. the results of the study show that the supervision strategy is good enough, supervision is carried out through online attendance. However, there are still obstacles such as the lack of maximum supervision carried out due to a lack of BKPSDM personnel in supervising ASN which exceeds the number of BKPSDM. The conclusion from this research is that the supervision strategy has been going well. but there are inhibiting aspects such as the lack of BKPSDM personnel in supervision.